Complementary methods for the prevention and treatment of stress-induced mastopathy - N. Chukhraev; Walery Zukow; N. Vladimirova; E. Chukhraeva; O. Tereshchenko (Kazimierz Wielki University, 2022)
The article considers the relationship between stress and diseases of the female reproductive system. A method for the rehabilitation of patients with mastopathy resulting from psycho-emotional stress (stress) based on the use of complementary methods of prevention and medical rehabilitation is proposed.